Growth, yield and quality of selected sweet potato (Ipomoea batatas [l.] Lam.), lines under varying soil moisture conditions - Ngugi, Penina; Masinde, Peter; Mworia, Eric (African Journal of Science, Technology and Social Sciences, 2022)
Sweet Potato (Ipomoea batatas [L.] has increasing potential as a food security crop in Kenya. However, its’ production is relatively low compared to its potential production which is attributed to drought conditions alongside use of local landrace cultivars that are quite low yielding. A study was conducted at Meru University of Science and Technology in Kenya in 2020-2021 to assess the performance of selected improved sweet potato lines under varied watering regimes. Two selected sweet potato varieties were used; CIP 106988.1 (Naspot13) and CIP 112286.1(Margarette), and a farmer-preferred variety Kemb-10. The varieties were subjected to three watering regimes (i) Severe stress (SS), 4 WAE (ii) Moderate Stress (MS), 9 WAE and (iii) well watered to maturity. A randomized complete block design in a split plot, with water treatment as the main plot and varieties as subplot with 3 replicates was used. There was no significant interaction between moisture treatments and varieties. Water treatments significantly (p≤0.05) affected vine length, number of leaves and tuber yield. Plants under severe stress had significantly lower vine length, branches and leaves. Under Moderate stress 9 WAE, plants experienced significant reduction in vine length, leaves and branches compared to the well watered. However, this reduction was less compared to severe stress. The reduced vine length and tuber yield is attributed to reduced cell division, elongation and assimilates partitioning. Tuber numbers correlated with leaves (r = 0.63*, 0.74*), and vine length (r = 0.62*, 0.76*). This positive correlation implies that if drought significantly reduces number of leaves and vine length, it reduces tuber yield indicating effect of drought on tuber yield can be estimated by measuring tuber length and number of leaves. Based on findings, ensuring the crop obtains enough moisture during the first nine weeks after planting is recommendable whereas Naspot13 is suitable for the area considering its higher productivity.